PREOCUPAÇÃO ÚLTIMA E AMBIENTE ÚLTIMO Aproximações possíveis entre Paul Tillich e James Fowler - SILVA JÚNIOR, ARMANDO ALTINO DA (2020)
This research aims to analyze the theology developed by James Fowler in his writings, mainly Stages of Faith, published in 1980, which points out the theologian Paul Tillich as an influencer of his work. Starting from Stages of Faith, the point is to observe the impact of Paul Tillich on James Fowler’s thinking and to draw attention to possible approximations between these two authors. The basis of this project is a possible approach between Paul Tillich’s “ultimate concern” and Fowler’s “ultimate environment” ideas. The main works analyzed are Dynamics of Faith by Paul Tillich and Stages of Faith by James Fowler, who has employed Tillich as the starting point for his book. We realize that “ultimate concern” is a well-defined and well-known concept, but we need to look for the grounds of the “ultimate environment” idea, so that we may see if there is any proximity between the authors in this regard. We realize that this theme is of great importance for the concepts of religion and faith, since the ultimacy would be the essential process that generates meaning to everything else in our existence. Therefore, we see that the synthesis that we may reach is an important increase for the study of the Sciences of Religion, primarily in a world that has experienced an immediate and utilitarian religiosity.